Influence of lithium bromide on electrical properties in bio-based polymer electrolytes - Ahmad Faizrin, Fuzlin; Sahraoui, B.; Ahmad Salihin, Samsudin (DRPM Universitas Indonesia, 2020)
The present work reports on the influence of lithium bromide (LiBr) in electrical properties of alginate, as bio-based polymer electrolytes (BBPEs) system. Alginate bio-based were prepared with various composition of LiBr via solution casting technique. The ionic conductivity and electrical properties of the prepared BBPEs samples were investigated using electrical impedance spectroscopy over a frequency range from 50 Hz to 1 MHz. The maximum ionic conductivity of 7.46 x 10-5 S cm-1 was obtained at ambient temperature (303 K) for sample containing with 15 wt. % lithium bromide-doped alginate bio-based polymer electrolytes. The electrical analysis revealed the highest ionic conductivity sample based alginate-LiBr BBPEs has the optimum dielectric constant and loss and increases significantly when temperature increased. The dielectric properties show that the entire alginate-LiBr BBPEs are in non-Debye behavior condition where there is no single relaxation occurred in the present system.